The rite of matrimony ("ordo qualiter agant illi qui nubere volunt") in the ritual of San Isidoro, León (Leoón, Archivo de la Real Colegiata de Sant Isidoro, cod. 12) - Carlin, Michael S. (Miscel·lània litúrgica catalana, 2018)
The rite of matrimony in the Ritual of San Isidoro, León (León, Archivo de la Real Colegiata de San Isidoro, cod. 12), dated 1187, presents important but much neglected evidence for how native Spanish liturgists negotiated the integration of new imported liturgical texts and ceremonies. Especially significant is the consent dialogue for both bride and groom, the first such text in any medieval European rite of matrimony. By situating this rite in the context of other contemporary Leonese and Castilian rites of matrimony, we can also begin to discern a common ritual milieu that shaped matrimony rites and practices in western Iberia.